A study of Confidence and Mathematical Problem Solving for grade eight students - Wangnongsiao, Patiwat; Thipchart, Yuthapong (Journal for Developing the Social and Community, 2024)
The purposes of this study were to (1) study the confidence of eighth grade students, (2) study the mathematical problem solving of eighth grade students, (3) study the relation between the self-confidence and Mathematical problems solving for eighth grade students. With a purposive sampling, purposive sampling were 83 students from the eighth grade class had two classes was 2/6 and 2/8, Sarakham Pittayakhom School, Mueang Maha Sarakham, Maha Sarakham province, Under the jurisdiction of the Secondary Educational Service Area Office 26. Research tools were a confidence test, a mathematical problem solving test, and an interview form of solving mathematical problems. Statistics for research were percentage, average, standard deviation, pearson correlation coefficient and a case study method. Data were presented through descriptive analytics. The results of the study were as follow: (1) the confidence level of most eighth grade students was at a moderate level, representing 66.26 percent, followed by a low level, it is 20.49 percent and is at a high level, represented as 13.25 percent (2) The mathematical problem solving of the eighth grade students mostly at mathematical problem solving is in fairly level, representing 49.40 percent, and (3) The relation between confidence and mathematical problem solving is a high level. With a correlation coefficient of .855 and from a study of the concept of finding answers among students with different levels of self-confidence. It was found that students at a high level Be confident in answering questions Problems are solved in a sequential and logical manner. Can explain thinking and problem solving. Students who are in the middle level Have some confidence in answering questions. And it cannot explain thinking and problem solving. But students are unable to solve complex problems. and students at a low-level Lack of confidence in answering questions There is no sequential and logical solution to the problem. Some people cannot explain their thinking and problem solving. Some people know how to solve problems but cannot use their thinking skills.